2012
DOI: 10.3329/icpj.v1i11.12062
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of RP-HPLC method for the estimation of omeprazole in bulk and capsule dosage forms

Abstract: A method for the determination of omeprazole in bulk and capsule dosage form by reverse phase high performance liquid chromatography has been developed. This is a simple, rapid, precise and an accurate method. The method was developed on a Novapak C18, (250 x 4.6 mm, 5µ) column using phosphate buffer (pH 7.4) and acetonitrile in the ratio of 60:40, v/v as a mobile phase which was pumped at a flow rate of 1.0 ml/min and detection was done at 302 nm. The retention time of the drug was found to be 7.71 min. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Several analytical methods have been described in literature for the determination of TIR in bulk, pharmaceutical and biological samples. These methods include UV spectrophotometry [4,5], HPLC [5][6][7][8][9], LC-MS [10,11] and TLC [5].…”
Section: Tirofiban Hydrochloride Monohydrate (Tir) a Non-peptide Molmentioning
confidence: 99%
“…Several analytical methods have been described in literature for the determination of TIR in bulk, pharmaceutical and biological samples. These methods include UV spectrophotometry [4,5], HPLC [5][6][7][8][9], LC-MS [10,11] and TLC [5].…”
Section: Tirofiban Hydrochloride Monohydrate (Tir) a Non-peptide Molmentioning
confidence: 99%
“…In the reaction optimization, some variables have been taken in the consideration that have great effect on the absorbance in order to get the higher, stable, and clear peak with good yield of product and fast preparation procedure of derivatization (Table 1). 5.0µg/mL FMOC-Cl spectrum in the reaction medium has three absorbance peaks (206, 264, 300nm), the 10.0µg/mL of OMZ has maximum absorbance 0.164 at 300nm, and the derivatization product profile has two absorbance region (217, and 300nm) and it is clearly observed that the absorbance peak has increased. Effect of the pH pH of the medium affects both FMOC-Cl and OMZ, in the alkaline media OMZ generates nucleophile and so the nucleophilic substitution reaction with FMOC-Cl will take a place, 29 also OMZ decomposes in the acidic media.…”
Section: Optimization Of the Reactionmentioning
confidence: 96%
“…Literature survey revealed that, there are several publication of omeprazole quantitative determination either individually or combined dosage form using various techniques, for instance, LC-MS/MS procedure for determination in drugs and metabolites in biological liquids such as urine and plasma, UPLC with UV detection method for determination of omeprazole in omeprazole magnesium blend, 3 FT-IR spectroscopic determination of omeprazole in combined dosage form, 4 RP-HPLC methods of determination, [5][6][7][8][9] HPLC quantitative methods of determination, [10][11][12][13][14] Capillary electrophoresis, 15 electrochemical methods, [16][17][18][19] spectrofluorometric methods 20 and spectrophotometric methods. [21][22][23][24][25][26][27] However, some methods have low sensitivity and accuracy.…”
mentioning
confidence: 99%
“…It has been suggested that sustained release dosage form of omeprazole may prolong the drug release for extended period of time and provide better therapeutic efficacy by inhibiting the regeneration of H + /K + -ATPase for longer duration (more than 3 days) in chronic acid related disorders. [11,13] In the present study, attempts have been made to develop co-processed pH dependent polymer for omeprazole drug in acidic environment as a stable delayed release tablet formulation and may give local effect in duodenal ulcer, reduced drug loss and also reduced dosing frequency due to sustained release of drug from the matrix.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[13] Instruments and reagents A prominence isocratic HPLC system (youngling HPLC YL 9000 series) with YL 9110 pump with autochro 3000 software and UV-VIS detector YL 9120 was used. Potassium dihydrogen orthophosphate and dipotassium hydrogen phosphate were of AR grade and acetonitrile and water of HPLC grade were used.…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%